Entrepreneurship skills application among ICT Graduates of Muni University, Uganda - Ritah, Nafuna; Nicholas, Nkamwesiga; Phelix, Businge Mbabazi (Kabale University Interdisciplinary Research Journal (KURJ), 2022)
The study aimed at investigating the acquisition and application levels of entrepreneurial skills acquired by ICT graduates from Muni University. This study specifically: identifies the entrepreneurial skills acquired by Muni University ICT Graduates; assess the entrepreneurial competency levels of Muni University ICT Graduates; examines the impact of the entrepreneurial skills acquired by Muni University ICT Graduates; evaluates the gaps in the entrepreneurial skills acquired among Muni University ICT Graduates. Questionnaires were administered to a population of 60 former students of Bachelor of Information Systems and Bachelor of Science in Information Technology who graduated from Muni University under the faculty of Technoscience. The graduates that formed the study population were selected, based on their online-availability, from two graduation cohorts of 2017 and 2018. Package for the Social Sciences (SPSS) (v.21) program was used to analyse the data. The research instrument was reliable at Chronbach’s alpha 0.960. The results of the study identified that the key entrepreneurship skills acquired by Muni University ICT graduates are: innovativeness; business and economic management; human relations and interpersonal skills; and communication skills. The study assessed the entrepreneurial competency levels of ICT graduates of Muni University rated against the industrial expectations. The results show that the graduates are competent in: computer literacy and information technology (ICT applications); creativity, innovation and opportunity identification; life skills (problem solving, time management, decision making, ability to learn and change management); literacy and numeracy among others. The study examined the impact of the entrepreneurial skills acquired by Muni University ICT Graduates and the results show that the graduates had: advanced in their career; acquired jobs; interest in setting their own business; the required knowledge to start businesses; demonstrated innovativeness and problemsolving ability. The study also evaluated the gaps in entrepreneurship skills acquired by ICT graduates of Muni University and the results indicate that the graduates had challenges in: getting finances or loans for starting a new business venture; communications like returning phone calls and emails; taking lead in a group and risk management. The ICT curriculum designers in Muni University should use the findings of this research to improve the curriculum in the courses that relate to entrepreneurship. There is need for the entrepreneurship learning facilitators to: train learners in numerical problem solving; equip learners with information and knowledge on business proposal writing and securing start-up finances; encourage learners to run and grow new business ventures. Acquisition of innovative skills such as creativity, critical thinking, analytical and problem-solving skills to ICT students for job creation should be upheld. In conclusion, ICT graduates of Muni University obtain the necessary entrepreneurial skills required by the ICT entrepreneurial industry. There is a need to continuously conduct more similar studies with other subsequent graduates in order to track the application of entrepreneurial skills by the ICT graduates of Muni University. The researchers also recommend an establishment of system to track Muni University alumni.